Upaya Meningkatkan Aktivitas Siswa dan Hasil Belajar Bahasa Arab melalui Contextual Teaching and Learning - Sunardi Sunardi (Nusantara: Jurnal Pendidikan Indonesia, 2022)
This research aims to improve student learning activities and outcomes after implementing the Contextual Teaching and Learning (CTL) learning method in learning Arabic for class XI-MIPA at MAN Kendal. This research is classroom action research. The subjects of this study were 34 students of class XI-MIPA-6 in the academic year 2021/2022. The research procedure includes 3 stages, namely: the preparation stage, the implementation stage, and the report preparation stage. Cycles 1 and 2 include planning, implementing actions, observing, and reflecting. Students who score above the KKM or who score more than 75 in accordance with student learning mastery, namely before the action was taken, 21 students (62%), in Cycle 1 rose to 26 students (76%) and in Cycle 2 it increased to 30 students (88%). Applying the CTL learning method combined with group discussion interactions can generate student learning activities. The achievement of student learning activity scores in cycle 1 reached 81% (very high) and in cycle 2 it reached 84% (very high). Based on the results of the analysis of student activities in group discussion interactions and student learning outcomes in providing actions with the application of the CTL learning method, it was found that there was an increase in learning activities and student learning outcomes.